2020
DOI: 10.1093/mnras/stz3459
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the coexistence of spin-up and spin-down behaviours in long-period X-ray pulsars

Abstract: Assuming wind-fed accretion magnetars in long-period X-ray pulsars, we calculated the rotational evolution of neutron stars. Our calculations considered the effects of magnetic field decay in magnetars. The results show that wind-fed accretion magnetars can evolve to long-period X-ray pulsars with a spin period much longer than 1000 s. The spin-down trend observed in 4U 2206+54-like sources is expected when young X-ray binary systems are on the way to their equilibrium period. Detailed calculations showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Alternatively, this overbraking could be indicative of a phase in the past in which stellar material was supplied to the neutron star at a much lower rate than today, and with a high amount of specific angular momentum, which is suggestive of a slow wind (Wang & Tong 2020;Ho et al 2020). The system would have been in the propeller regime, and the neutron star would have spun down until the mass accretion rate suddenly increased by so much that the magnetospheric radius became smaller than the corotation radius, as is currently observed if the magnetic field measured through CRSFs is accurate.…”
Section: Magnetospheric Accretion and Induced Torquesmentioning
confidence: 99%
“…Alternatively, this overbraking could be indicative of a phase in the past in which stellar material was supplied to the neutron star at a much lower rate than today, and with a high amount of specific angular momentum, which is suggestive of a slow wind (Wang & Tong 2020;Ho et al 2020). The system would have been in the propeller regime, and the neutron star would have spun down until the mass accretion rate suddenly increased by so much that the magnetospheric radius became smaller than the corotation radius, as is currently observed if the magnetic field measured through CRSFs is accurate.…”
Section: Magnetospheric Accretion and Induced Torquesmentioning
confidence: 99%
“…Finally, although our estimates of the spin period were inconclusive in terms of the spin evolution of the pulsar, future monitoring programs are essential for determining whether the pulsar is spinning up or down. It has been proposed that long-period pulsars with magnetar-like field strengths could exhibit a spin up trend due to the decay of the B field of the NS (Wang & Tong 2020). A future measurement of the spin evolution will therefore provide crucial information about the nature of the NS.…”
Section: A Highly Magnetised Slowly Rotating Neutron Star?mentioning
confidence: 99%
“…Observations of X-ray pulsars have indicated that they have spin periods ranging from milli-seconds (for example, SAX J1808.4+3658, Wijnands & van der Klis 1998) all the way up to a few thousand seconds (for example, 4U2206+54, 2S 0114+65, see Wang & Tong 2020). In fact, recent studies have indicated that the Be X-ray binary population comprises of two sub populations based on their spin and orbital periods and orbital eccentricities (Knigge, Coe & Podsiadlowski 2011): i) the short spin Pspin ∼ 10 s, P orb ∼40 d, and ii) Pspin ∼ 200 s, P orb ≈ 100 d (Prišegen 2020).…”
Section: Introductionmentioning
confidence: 99%